Exploring Reduce, Recycle and Reuse (3Rs) Awareness, Practice among Oil and Gas Workers and its Influence on Their Productivity - Rashid, Mas Anom Abd; Othman, Mohd Noor Azman; Rashid, Saidatul Shahida; Ali, Mohamad Bilal (International Journal of Economics and Financial Issues, 2015)
One of the approaches to reduce waste generated is reduce, recycle and reuse (3R) method. The reduction in waste generated or increase in recycling rates reflects the success of both the government and voluntary public participation. Nowadays, developed and developing countries are trying to find out new ways for climate change mitigation and adaptation options. Developing countries like Malaysia must also look for options to lessen the climate change effect and at the same time increase office productivity particularly on the ways the employees managed their supplies, resources and generated waste. This study is conducted on the office employees at Petronas Berhad with regards to how the manage the generated waste. It is aimed to determine the level of employees’ awareness and attitude towards 3R and determine its influence on their productivity. It was found that the employees have a high level of awareness on 3R, yet their practices are at the low to moderate levels. The authors believed that this could due to the management’s support towards the 3R is not as high as expected by the office employees. Keywords: Recycle; Reuse; Awareness; Waste Generated; Productivity JEL Classifications: Q4; Q5